Ուրարտերենի որոշ բառաքննական դիտարկումներ և ստուգաբանություններ - Այվազյան, Սարգիս (ԳԱԱ ԼԻ հրատ․)
Many of the approximately 600 Urartian words that have come down to us either have no translation at all or the existing translations are tentative and ambiguous. This article attempts to translate some of these words or clarify existing meanings. The translations and clarifications are made by comparing the original Urartian texts and data from the old Armenian language. This method allows for more accurate translations of these Urartian words and their etymological analysis․ Многие из примерно 600 дошедших до нас урартских слов либо не имеют перевода, либо существующие переводы носят предположительный и неоднозначный характер. В данной статье предпринята попытка перевести некоторые из этих слов или уточнить их значения. Переводы и уточнения сделаны путем сопоставления оригинальных урартских текстов и данных древнеармянского языка. Этот метод позволяет получить более точные переводы этих урартских слов и провести их этимологический анализ.
Keywords: Հայոց լեզու; Լեզվաբանություն